Effects of Recombinant Angiogenin on Collagen Fiber Formation and Angiogenesis in the Dermis of Wistar Rats - Yurina NV; Ageeva TA; Goryachkin AM; Varaksin NA; Ryabicheva TG; Ostanin AA; Chernykh ER; Romashchenko AV; Proskurina AS; Bogachev S; Purtov AV (Dove Medical Press, 2021)
Natalia V Yurina,1 Tatiana A Ageeva,2 Aleksandr M Goryachkin,2 Nikolay A Varaksin,3 Tatiana G Ryabicheva,3 Alexandr A Ostanin,4 Elena R Chernykh,4 Alexander V Romashchenko,5 Anastasia S Proskurina,5 Sergey Bogachev,5 Alexey V Purtov6 1Autonomous Non-Profit Organization “Regional Center for High Medical Technologies”, Novosibirsk, Russia; 2Novosibirsk State Medical University, Novosibirsk, Russia; 3JSC “Vector-Best”, Novosibirsk, Russia; 4Research Institute of Fundamental and Clinical Immunology, Novosibirsk, Russia; 5Institute of Cytology and Genetics, Siberian Branch of the Russian Academy of Sciences, Novosibirsk, Russia; 6LLC “Angiopharm Laboratory”, Novosibirsk, RussiaCorrespondence: Sergey Bogachev Email labmolbiol@mail.ruPurpose: The purpose of this study was to assess the capability of recombinant angiogenin isolated from Pichia pastoris yeasts to stimulate regenerative processes in the dermis of experimental animals.Patients and Methods: Wistar rats were administered with recombinant angiogenin intracutaneously. Morphological examination of the skin and the assessment of the proliferative activity of the epidermal cells were carried out. Additionally, cytokine production by human whole blood cells exposed to angiogenin was analyzed ex vivo.Results: Administration of angiogenin stimulates collagen fiber formation and angiogenesis. This stimulation is tightly associated with an increase in the number of fibroblasts, an increased numerical density of dermal blood vessels and an increased density of collagen fibers; also, it activates the proliferation of basal cells. Angiogenin induces the production of MCP, IL-8, IL-6, IL-1β, TNF-α, IL-10, TGF-β, and VEGF by blood cells.Conclusion: The results obtained indicate a broad spectrum of actions of recombinant angiogenin during regenerative processes in the basal layer of the dermis.Keywords: intracutaneous injections, pathomorphological analysis, cytokines, regeneration